Perhitungan produktipitas tanah Propinsi Dati I Jawa Tengah (Publikasi (Indonesia. Direktorat Tata Guna Tanah) ;, 1982)
Data on productivity of land for agricultural purposes in Jawa Tengah; by type of land use and kabupaten.